Effectiveness of different bracing systems to prevent exterior girder rotation during bridge deck construction. (1st July 2017) - Ashiquzzaman, Md; Calvo, Carlos Merino; Hui, Li; Ibrahim, Ahmed; Lindquist, Will; Hindi, Riyadh
Highlights: Exterior girder rotations during bridge constructions have been monitored. Different configurations of bracing systems are investigated experimentally. Existing bridge bracing systems have been evaluated using FEM and field monitoring. New proposed bracing configurations for minimal girder rotations during construction. Abstract: Different bracing systems are currently being used by bridge contractors to prevent exterior girder rotation that can occur during bridge construction. This rotation is caused by unbalanced eccentric loads from the deck overhang. These eccentric loads cause exterior girders to twist which may result in several problems during construction or over the life of the bridge. Contractors generally use block-and-tie systems which are formed with different combinations of reinforcing bars and timber blocks to limit twisting of the exterior girders. Block-and-tie systems do not always work as expected, and their efficacy in preventing rotation has not been fully evaluated. In this research, different configurations and types of bracing systems are investigated experimentally to compare their effectiveness with the current block-and-tie methodology. Specimens are loaded eccentrically to simulate the overhang load that causes rotation in the field. Forty-five bracing combinations were tested and evaluated by varying the number of bracing elements and spacing among them. The measured rotation values for all cases were obtained experimentally from loaded exterior girder at mid span. The experimental results demonstrated the lack of effectiveness of the current block-and-tie systems. Adjustable diagonal steel pipes, permanent intermediate cross-frames, or both were tested as alternatives and showed notable reductions in girder rotation. Finally, finite element models (FEM) were developed using ABAQUS/standard to replicate the experimental results followed by additional analysis using the validated FE model. The results from the experiment and the FEA highlight deficiencies in the current block-and-tie systems and present three improved rotation prevention systems.